Percentage of Attacks and Intensity of Damage by Emerald Beetle Pest Agrilus sp. (Coleoptera: Buprestidae) on Clove Plantations in Pinolosian District, South Bolaang Mongondow Regency - Watung, Jackson; Umboh, Ulrich; Tarore, Dantje; Dumalang, Sherlij (Sam Ratulangi University, 2025)
Clove (Syzygium aromaticum (L) Merr.& Perry) is an aromatic shrub. In 2007, a stem-boring beetle, namely the emerald beetle Agrilus sp. (Coleoptera: Buprestidae), was found in Pinolosian Subdistrict, South Bolaang Mongondow Regency. This study aims to determine the intensity of damage and the percentage of Agrilus sp. pest infestation in Pinolosian Subdistrict, South Bolaang Mongondow Regency. The study was conducted in Pinolosian District, South Bolaang Mongondow Regency, North Sulawesi Province, from February to July 2025. The study employed a quantitative descriptive method. Data on the percentage of infestation and damage intensity caused by Agrilus sp. were processed using Microsoft Excel and presented in tables and diagrams. The highest percentage of infestation was found at Station III at 70%, The highest attack percentage was found at Station III at 70%, and the lowest attack percentage was found at Station II at 40%. The highest damage intensity was found at Station III at 50.83% with a severe damage category, and the lowest damage intensity was found at Station II at 12.50% with a mild damage category. Keywords: Attack percentage, damage intensity, and Agrilus sp. Abstrak. Cengkeh (Syzygium aromaticum (L.) Merr. & Perry) adalah tanaman perdu beraroma. Pada tahun 2007 ditemukan kumbang penggerek batang yaitu kumbang zamrud Agrilus sp. (Coleoptera: Buprestidae) di Kecamatan Pinolosian, Kabupaten Bolaang Mongondow Selatan. Penelitian ini bertujuan untuk mengetahui intensitas kerusakan dan persentase serangan hama Agrilus sp. di Kecamatan Pinolosian, Kabupaten Bolaang Mongondow Selatan. Penelitian ini dilaksanakan di Kecamatan Pinolosian, Kabupaten Bolaang Mongondow Selatan, Provinsi Sulawesi Utara dan dilaksanakan pada bulan Februari-Juli 2025. Penelitian ini menggunakan metode deskriptif kuantitatif. Data persentase serangan dan intensitas kerusakan hama Agrilus sp. diolah menggunakan Ms. Excel dan ditampilkan dalam bentuk tabel dan diagram. Persentase serangan tertinggi terdapat pada Stasiun III yaitu 70%, dan persentase serangan terendah ditemukan pada Stasiun II yaitu 40%. Intensitas kerusakan tertinggi terdapat pada Stasiun III yaitu 50,83% dengan kategori kerusakan berat, dan intensitas kerusakan terendah ditemukan di Stasiun II yaitu 12,50% dengan kategori kerusakan ringan. Kata Kunci: Persentase serangan, Intensitas kerusakan, dan Agrilus sp